Cutting down on the ozone and SOA formation as well as health risks of VOCs emitted from e-waste dismantlement by integration technique. (1st November 2019) - Liu, Ranran; Chen, Jiangyao; Li, Guiying; Wang, Xinming; An, Taicheng
Abstract: Elimination of volatile organic compounds (VOCs) in the e-waste dismantling industry by an integration technique of spray tower-electrostatic precipitation-photocatalysis was conducted to investigate its application possibility for reducing formation of O3 and secondary organic aerosols (SOAs) as well as exposure risk. Results revealed the average 5.4 × 10 2  μg m −3 of VOCs with the top two groups being aromatic hydrocarbons (AHs, 55.93%) and halogenated hydrocarbons (HHs, 33.33%), contributing to 1.3 × 10 3 and 3.0 × 10 4  μg m −3 of the O3 and SOA (OFP and SOAFP) formation potential, respectively. Furthermore, 86.47% of OFP and 99.87% of SOAFP were ascribed to AHs, in which toluene ranked first (35.30% and 48.07%). The highest removal efficiency (76.92%) for VOCs by the integrated technique resulted in excellent prevention efficiencies of OFP (71.54%) and SOAFP (80.62%). Occupational cancer risk assessment found that HHs (62.63%) and AHs (36.93%) were the top two contributors. After the treatment by the integrated technique, 55.44% of the total risk index was reduced with the accumulation of few low-concentrated and more toxic AHs (e.g. 6.6 μg m −3 benzene on average). All results suggest that controlling AH and HH emissions from the e-waste dismantling source could efficiently prevent atmospheric secondary pollution and human exposure risk to industrial emission. Graphical abstract: Image 1 Highlights: Emitted toluene mainly contributes to ozone and secondary organic aerosol formation. Remove aromatic VOCs facilitate to cut down O3 and secondary organic aerosol formation. Purifying halogenated and aromatic hydrocarbons can fast reduce cancer exposure risk.